Skin sloughing in susceptible and resistant amphibians regulates infection with a fungal pathogen - Michel E. B. Ohmer (Nature Portfolio, 2017)
The fungal pathogen Batrachochytrium dendrobatidis (Bd) has been implicated in amphibian population declines globally. Given that Bd infection is limited to the skin in post-metamorphic amphibians, routine skin sloughing may regulate infection. Skin sloughing has been shown to reduce the number of cultivatable microbes on amphibian skin, and Bd infection increases skin sloughing rates at high loads. However, it is unclear whether species specific differences in skin sloughing patterns could regulate Bd population growth on the skin, and influence subsequent infection dynamics. We exposed five Australian frog species to Bd, and monitored sloughing rates and infection loads over time. Sloughing reduced Bd load on the ventral skin surface, in all five species, despite wide variation in susceptibility to disease. In the least susceptible species, an increase in sloughing rate occurred at lower infection loads, and sloughing reduced Bd load up to 100%, leading to infection clearance. Conversely, the drop in Bd load with sloughing was only temporary in the more susceptible species. These findings indicate that the ability of sloughing to act as an effective immune defence is species specific, and they have implications for understanding the pattern of Bd population growth on individual hosts, as well as population-level effects.